Structural, magnetic and electronic properties of Fe1+xGa2−xO4 nanoparticles synthesized by the combustion method. Issue 32 (26th July 2016) - Lyubutin, I. S.; Starchikov, S. S.; Gervits, N. E.; Lin, Chun-Rong; Tseng, Yaw-Teng; Shih, Kun-Yauh; Lee, Jiann-Shing; Ogarkova, Yu. L.; Korotkov, N. Yu.
Abstract : Gallium-ferrite Fe1+ x Ga2− x O4 nanoparticles consisting of a combination of FeGa2 O4 and a new spinel phase γ-FeGaO3 have been synthesized by the combustion method. Abstract : The combustion method was used to prepare a precursor powder of an iron-gallium oxide compound which was further heat-treated in order to obtain a set of Fe1+ x Ga2− x O4 nanoparticles. All samples have a cubic spinel-type structure (space group Fd 3̄ m ) and the particle size varies from 1.8 to 28.0 nm depending on the treatment conditions. From the comparative analysis by XRD, EDS, and Raman and Mössbauer spectroscopy the creation of a new spinel phase γ-FeGaO3, which was mainly located on the particle surface, was established. As a result, the composition consists of a FeGa2 O4 core covered by a FeGaO3 shell. The relative content of FeGa2 O4 /FeGaO3 compounds in the composites can be varied by heat treatment. The maximum in the ZFC magnetization curves appeared in all samples at about 20–30 K corresponding to the spin-freezing temperature T sg, which is much higher than in the bulk compound with a pure inverse spinel structure (Ga)[FeGa]O4 . The values of effective Curie temperature Θ C for the Fe1+ x Ga2− x O4 nanoparticles are rather high and positive, indicating a ferromagnetic interaction between iron ions. The high values of the magnetic frustration parameter f = Θ C /T sg (up to 7) indicate a high degree of magnetic frustration. The low temperature Mössbauer data reveal the magnetic ordering of Fe ions in all samples with the magnetic transition at about 20–26 K depending on the particle size. The specific features of the Mössbauer parameters indicate the properties of non-homogeneous magnetic systems with frustrated interactions specific to spin-glasses. The magnetic system behaves as a spin-glass below T sg and it is superparamagnetic above T sg . Such a system is called a " super-spin-glass ". The anisotropy energy E anis strongly depends on the content of Fe 2+ and Fe 3+ ions which contribute to the magnetocrystalline E cryst and exchange E ex anisotropies, respectively. The anisotropy energy can be tuned by variation of the content of the (FeGaO3 )–(FeGa2 O4 ) phases in these complex composites.